2021
DOI: 10.1002/cti2.1324
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic programming underpins B‐cell dysfunction in peanut and multi‐food allergy

Abstract: Objective Rates of IgE‐mediated food allergy (FA) have increased over the last few decades, and mounting evidence implicates disruption of epigenetic profiles in various immune cell types in FA development. Recent data implicate B‐cell dysfunction in FA; however, few studies have examined epigenetic changes within these cells. Methods We assessed epigenetic and transcriptomic profiles in purified B cells from adolescents with FA, comparing single‐food‐allergic (peanut only), multi‐food‐allergic (peanut and ≥1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 99 publications
0
27
0
Order By: Relevance
“… 12 The AIM2 gene is related to the hyperinflammatory manifestation of MIS-C patients since triggers caspase-1 and unleashes pro-inflammatory cytokines such as IL-1β and IL-18, 19 which are also involved in the innate immune response to viral infections. Regarding PM20D1, recent data suggest that it contributes to autoimmune disorders and allergies, 20 , 21 all of which are pathologies with an important hyperinflammatory component. In this study, we have identified that a DNA methylation site of the HLA-DRB1 (major histocompatibility complex, class II, DR beta 1) gene is linked to MIS-C. Interestingly, our study of adult COVID-19 cases identified that an epigenetic mark in HLA-C (major histocompatibility complex, class I, C) was associated with the severe disease.…”
Section: Resultsmentioning
confidence: 99%
“… 12 The AIM2 gene is related to the hyperinflammatory manifestation of MIS-C patients since triggers caspase-1 and unleashes pro-inflammatory cytokines such as IL-1β and IL-18, 19 which are also involved in the innate immune response to viral infections. Regarding PM20D1, recent data suggest that it contributes to autoimmune disorders and allergies, 20 , 21 all of which are pathologies with an important hyperinflammatory component. In this study, we have identified that a DNA methylation site of the HLA-DRB1 (major histocompatibility complex, class II, DR beta 1) gene is linked to MIS-C. Interestingly, our study of adult COVID-19 cases identified that an epigenetic mark in HLA-C (major histocompatibility complex, class I, C) was associated with the severe disease.…”
Section: Resultsmentioning
confidence: 99%
“…The results suggested that B cells from peanut patients showed specific epigenetic and gene expression differences relative to non-allergic patients. Furthermore, these results suggested that single-peanutallergic and multi-food patients possessed unique group-specific epigenetic signatures involving differential regulation of B-and T-cell development, B-cell lineage determination and tumor growth factor beta (TGF-β) signaling pathway, highlighting the phenotypic and molecular distinction of the multi-food clinical group from single-peanut-allergic patients [50]. However, another work has shown promising data regarding gene expression differences between diverse FA endotypes and control patients.…”
Section: Peanut Allergymentioning
confidence: 98%
“…Among those is asthma, where the hypomethylation of probe cg14893161 was initially shown in babies born to mothers with asthma and atopic mothers without asthma [86] . A direct association between hypermethylation of PM20D1 and respiratory allergy, specifically for probe cg11965913, has also been identified; expression of PM20D1 is regulated by the TLR5 pathway, which is closely related to allergic responses [87] . In addition to a respiratory allergic response, hypomethylation in the gene has also been associated with food allergies [88] .…”
Section: Other Phenotypesmentioning
confidence: 99%